Circulating parathyroid hormone and serotonin in multiparous cows with differing postparturient serum calcium concentrations - C.R. Seely; J.A.A. McArt (Journal of Dairy Science, 2023)
ABSTRACT: Many multiparous dairy cows experience subclinical hypocalcemia (SCH) in the immediate postpartum period as they adapt to the demands of lactation. Furthermore, differing dynamics of SCH in the days following parturition are associated with varied health and production outcomes, with cows experiencing transient SCH producing more milk and facing fewer negative health events than cows with delayed or persistent SCH. Our objectives were to describe differences in mediators of calcium (Ca) homeostasis between cows experiencing differing Ca dynamics postpartum. A prospective cohort of 89 multiparous Holstein cows from 2 herds in New York were classified into 1 of 4 SCH groups based on mean serum total Ca (tCa) at 1 and 4 d in milk (DIM): normocalcemic (NC; [tCa] >1.89 mmol/L at 1 DIM and >2.25 mmol/L at 4 DIM, n = 30); transient SCH (tSCH; [tCa] ≤1.89 mmol/L at 1 DIM and >2.25 mmol/L at 4 DIM, n = 12); delayed SCH (dSCH; [tCa] >1.89 mmol/L at 1 DIM and ≤2.25 mmol/L at 4 DIM, n = 23); and persistent SCH (pSCH; [tCa] ≤1.89 mmol at 1 DIM and ≤2.25 mmol/L at 4 DIM, n = 24). Blood samples were collected at −5, −1, 1 through 5, 7, and 10 DIM and analyzed for tCa, parathyroid hormone (PTH), and serotonin. Repeated measures ANOVA models were used to analyze differences between SCH groups and changes over time for tCa, PTH, and serotonin. During the prepartum period, tCa was greater in the NC, tSCH, and dSCH cows as compared with the pSCH cows and there was marginal evidence for a difference in PTH between SCH groups. Postpartum tCa varied over time between SCH groups. Mean postpartum (95% confidence interval) tCa for respective SCH groups were NC = 2.32 (2.28, 2.35) mmol/L; tSCH = 2.20 (2.14, 2.25) mmol/L; dSCH = 2.17 (2.13, 2.21) mmol/L; and pSCH = 2.03 (1.99, 2.07) mmol/L. Mean concentrations of PTH in the postpartum period were NC = 70.1 (66.2, 74.4) pmol/L; tSCH = 72.1 (66.1, 79.2); dSCH = 75.8 (70.8, 81.5) pmol/L; and pSCH = 77.7 (72.4, 83.9) pmol/L. Serotonin was similar between SCH groups pre- and postpartum and followed a cyclical pattern from 1 to 10 DIM. Our results agreed with our hypothesis that differences in postpartum PTH might exist between cows experiencing different dynamics of SCH in the early lactation period; however, further studies are needed to confirm this difference. If true, this would suggest that Ca homeostasis may be disrupted in cows with dSCH and pSCH. Gaining a better understanding of these modulatory differences may aid in the prevention, management, and treatment of SCH.